PAEDIATRIC ADVERSE DRUG REACTIONS (ADRS): A COMPARISON OF A NEWLY DEVELOPED AVOIDABILITY TOOL TO EXISTING HALLAS ASSESSMENTS. Issue 9 (17th August 2016) - Bracken, Louise; Kirkham, Jamie; Nunn, Anthony; Pirmohamed, Munir; Peak, Matthew; Turner, Mark
Abstract : Aim: To compare a newly developed avoidability assessment tool (AAT) to existing Hallas assessments1 for a set of paediatric ADR cases. Method: The new AAT was employed to assess 249 case reports of ADRs causing admission to hospital. The case reports contained a description of the ADR, details of suspected and concurrent medication and past medical history. Each case report was independently assessed and an avoidability category assigned. For ADRs categorised as either 'possibly' or 'definitely avoidable' a rationale was recorded. A second reviewer independently assessed a purposive sample (10%) for validation and quality assurance purposes. The final outcome was then compared to the Hallas assessments (1) previously completed as part of another study, which was carried out in a consensus group setting. Both tools used categorical scores with the same four point ordinal scale 'definitely avoidable', 'possibly avoidable', 'not avoidable' and 'unassessable'. Results: Assessment of the 249 ADR case reports using the new AAT found that 19.3% were either possibly or definitely avoidable. This figure increased to almost 32% for the non-oncology cases (129/249) and decreased to 5.8% for the oncology cases (120/249). This was similar to the Hallas results (1), where overall, 22% of ADRs were deemed either possibly or definitely avoidable. Percentage exact agreement (%EA) was 90% overall; when subcategorised into oncology and non-oncology cases the %EA was found to be 94.2% and 86% respectively. Percentage extreme disagreement (%ED) was 0.8%. The kappa score was 0.71 (95% CI 0.60–0.82) for all cases, 0.54 (95% CI 0.40–0.68) for the oncology cases and 0.73 (95% CI 0.58–0.88) for the non-oncology cases. In total there were 25/249 cases with disagreement. %EA agreement from the validation check was 72%. Conclusion: Assessment with the new AAT showed that approximately 19% of all cases were either possibly or definitely avoidable. This was comparable to the Hallas assessments (1). The sub-categorisation of the analysis into oncology and non-oncology cases showed a change in the number of avoidable cases. The avoidability rate increased to almost 32% for the non-oncology cases and decreased to 5.8% for the oncology cases. The reason for this marked difference may be explained by the nature of the oncology ADRs. The most common oncology reactions were neutropenia, thrombocytopenia and anaemia; these are often expected and largely 'not avoidable' given the benefit risk ratio. The AAT was designed specifically for use in paediatrics following difficulty using other tools including Hallas (1). The AAT refers to guidelines and patient history rather than to abstract concepts such as "present-day knowledge of good medical practice" and "effort exceeding the obligatory demands" as per Hallas (1). Further work to identify potentially avoidable ADRs and strategies to prevent them is needed.